2021
DOI: 10.3390/rs13122357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the MODIS (C6) Daily Albedo Products for Livingston Island, Antarctic

Abstract: Although extensive research of Moderate Resolution Imaging Spectroradiometer (MODIS) albedo data is available on the Greenland Ice Sheet, there is a lack of studies evaluating MODIS albedo products over Antarctica. In this paper, MOD10A1, MYD10A1, and MCD43 (C6) daily albedo products were compared with the in situ albedo data on Livingston Island, South Shetland Islands (SSI), Antarctica, from 2006 to 2015, for both all-sky and clear-sky conditions, and for the entire study period and only the southern summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…In fact, in other polar regions, such as Svalbard, considerably higher error values have been obtained on cloudy days (7 K) than on clear days (3 K) when comparing MODIS LST with T s measurements [75]. This masking effect of the in situ measurement real value had already been described for LST in Siberia [80] and it has been verified that the same occurs with the albedo in our study area: the cloud mask failure can cause MODIS estimate to correspond to cloud albedo values and not snow albedo values [81].…”
Section: Discussionsupporting
confidence: 82%
“…In fact, in other polar regions, such as Svalbard, considerably higher error values have been obtained on cloudy days (7 K) than on clear days (3 K) when comparing MODIS LST with T s measurements [75]. This masking effect of the in situ measurement real value had already been described for LST in Siberia [80] and it has been verified that the same occurs with the albedo in our study area: the cloud mask failure can cause MODIS estimate to correspond to cloud albedo values and not snow albedo values [81].…”
Section: Discussionsupporting
confidence: 82%
“…The albedo analysis showed a slight increase in this variable in the period 2006-2015 of 2% and 6% in the in situ and MODIS data, respectively, which was explained by an increase of snowfall along with a decrease in snowmelt in the study area and the temporal period [26]. Several MODIS daily albedo products were evaluated, and it was concluded that the best correlation between the in situ and MODIS data was obtained with the MOD10A1 product [27]. The temperature analysis in the Hurd Peninsula of Livingston Island is presented in this article and will also contribute to the study of the permafrost, because its thermal behavior and evolution are directly related to the weather and climate conditions, especially when there is no vegetation on the soil surface, which is the case in most of the permafrost areas in Antarctica [24].…”
Section: Introductionmentioning
confidence: 93%
“…We also use the Kain–Fritsch scheme for cumulus parameterization (only for domain 1) and Noah‐MP for the land surface model (Kain, 2004; Niu et al., 2011). Most importantly, REMA 1 km topography information and MODIS observed surface albedo, described previously, are included in the input data to provide a better surface description (Howat et al., 2019; Corbea‐Pérez et al., 2021; Figure S1 in Supporting Information ). To avoid model instabilities, topographic smoothing has been applied to PWRF simulations.…”
Section: Methodsmentioning
confidence: 99%